Pengaruh Religiusitas Obligation, Literasi Halal dan Label Halal terhadap Persepsi Mahasiswa dalam Mengonsumsi Produk Ikan Sardines Kaleng AbC dengan Brand Awarness Sebagai Variabel Moderating - Wardani, Ali; Wahab, Abdul; Syahruddin; Ahmad Fauzan (Universitas Islam Negeri Alauddin Makassar, 2024)
The circulation of food mixed with non-halal ingredients forces Muslim consumers to have good perceptions of halal food. This study attempts to analyse the factors (religiosity obligation, halal literacy and halal label) in influencing the perception of halal food. This type of research is quantitative research with an associative approach. The results of the study concluded that religiosity obligation, halal literacy and halal labels have a significant positive effect on the perception of halal food for Muslim consumers. Brand awarness, although moderating the relationship between the halal label and the perception of halal food, on the other hand, does not moderate the relationship between religiosity obligation and halal literacy with the perception of halal food for Muslim consumers. This means that although the current research trend is that halal literacy has no effect on the perception of halal food, this study concludes otherwise, namely halal literacy has a significant positive effect on the perception of halal food. This conclusion is very useful for halal food producers in increasing sales through halal labels and increasing brand awarness through advertising or increasing halal literacy of Muslim consumers.